2004
DOI: 10.1103/physrevc.69.044321
|View full text |Cite
|
Sign up to set email alerts
|

Superscaling in nuclei: A search for a scaling function beyond the relativistic Fermi gas model

Abstract: We construct a scaling function f͑Ј͒ for inclusive electron scattering from nuclei within the coherent density fluctuation model (CDFM). The latter is a natural extension to finite nuclei of the relativistic Fermi gas model within which the scaling variable Ј was introduced by Donnelly and collaborators. The calculations show that the high-momentum components of the nucleon momentum distribution in the CDFM and their similarity for different nuclei lead to quantitative description of the superscaling in nuclei… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
123
1

Year Published

2006
2006
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(136 citation statements)
references
References 32 publications
12
123
1
Order By: Relevance
“…As already mentioned in previous work [16], this asymmetry of the RMF description constitutes a basic difference from other models presented in the literature [55][56][57] where the long tail in f (ψ ) is largely absent.…”
Section: Camentioning
confidence: 48%
See 1 more Smart Citation
“…As already mentioned in previous work [16], this asymmetry of the RMF description constitutes a basic difference from other models presented in the literature [55][56][57] where the long tail in f (ψ ) is largely absent.…”
Section: Camentioning
confidence: 48%
“…Ingredients beyond the impulse approximation, i.e., multinucleon knockout, either induced by exchange currents, correlations, or rescattering effects, are surely needed to get more strength in the scaling function which will be then closer to the experiment. This is in fact the case of the coherent density fluctuation model (CDFM) for correlations presented in [55][56][57]. This model is an extension of the RFG applied to finite nuclei, and its prediction is also shown for comparison in Fig.…”
Section: B Inclusive Qe Charged-current (ν µ) Reactionsmentioning
confidence: 99%
“…The CDFM has been applied to studies of the superscaling phenomenon [20][21][22][23] in inclusive electron-nucleus scattering, as well as to analyses of neutrino and antineutrino scattering by nuclei of both charge-changing [23,35] and neutral-current [36] types. Before entering into a discussion of the RMF results, it is interesting to point out the significant differences introduced by the other models.…”
Section: Scaling Function In Relation To the Spectral Function Anmentioning
confidence: 99%
“…Since it is impossible within the MFA to describe simultaneously the density and momentum distributions in nuclei [4,[7][8][9][10][11][12], a consistent analysis of the role of the NN correlations is required using theoretical methods that go beyond the MFA to obtain a successful description of the relevant experiments. The present study uses the results found from studies of y scaling [1][2][3][13][14][15] and superscaling (based on ψ-scaling variable) [15][16][17][18][19][20][21][22][23] obtained from analyses of inclusive electron scattering data. The latter consists in constructing a "superscaling function" f (ψ) obtained by removing the single-nucleon content from the double-differential cross section and plotting it versus a scaling variable ψ(q, ω).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation